The effect of startle reflex habituation on cardiac defense: Interference between two protective reflexes - Fernández, M.; Vila, J.; Lipp, Ottmar; Purkis, H. (Elsevier BV, 2008)
The present study investigated the relationship between blink startle and cardiac defense, two protective reflexes that are said to be elicited by the transient and the sustained components, respectively, of high intensity stimuli. Three groups of participants were presented with three intense long lasting noise stimuli (500ms) after habituation training with 12 brief (50ms) high intensity noise bursts (High group), low intensity noise bursts (Low group) or high intensity visual stimuli (Light group). The transition from habituation to defense stimuli resulted in increased blink startles in groups Low and Light, but not in group High. A cardiac defense reflex, characterised by a short and long delayed increase in heart rate, was observed in group Light, but not in groups Low and High. This pattern of results indicates that habituation to startle eliciting stimuli will impair defense reflexes elicited on subsequent test trials and suggests some interrelation between the two reflex systems. © 2008 Elsevier B.V. All rights reserved.